Antibody-Antigen Binding Interface Analysis in the Big Data Era - Reis, Pedro B. P. S.; Barletta, German P.; Gagliardi, Luca; Fortuna, Sara; Soler, Miguel A.; Rocchia, Walter (Frontiers in Molecular Biosciences, 2022)
Antibodies have become the Swiss Army tool for molecular biology and nanotechnology. Their outstanding ability to specifically recognise molecular antigens allows their use in many different applications from medicine to the industry. Moreover, the improvement of conventional structural biology techniques (e.g., X-ray, NMR) as well as the emergence of new ones (e.g., Cryo-EM), have permitted in the last years a notable increase of resolved antibody-antigen structures. This offers a unique opportunity to perform an exhaustive structural analysis of antibody-antigen interfaces by employing the large amount of data available nowadays. To leverage this factor, different geometric as well as chemical descriptors were evaluated to perform a comprehensive characterization.